Non-linear Scaling of Passive Mechanical Properties in Fibers, Bundles, Fascicles and Whole Rabbit Muscles - Ward, Samuel R.; Winters, Taylor M.; O’Connor, Shawn M.; Lieber, Richard L. (Frontiers in Physiology, 2020)
Defining variations in skeletal muscle passive mechanical properties at different size scales ranging from single muscle fibers to whole muscles is required in order to understand passive muscle function. It is also of interest from a muscle structural point-of-view to identify the source(s) of passive tension that function at each scale. Thus, we measured passive mechanical properties of single fibers, fiber bundles, fascicles, and whole muscles in three architecturally diverse muscles from New Zealand White rabbits (n=6) subjected to linear deformation. Passive modulus was quantified at sarcomere lengths across the muscle’s anatomical range. Titin molecular mass and collagen content were also quantified at each size scale, and whole muscle architectural properties were measured. Passive modulus increased nonlinearly from fiber to whole muscle for all three muscles emphasizing extracellular sources of passive tension (p<0.001), and was different among muscles (p<0.001), with significant muscle by size-scale interaction, indicating quantitatively different scaling for each muscle (p<0.001). These findings provide insight into the structural basis of passive tension and suggest that the extracellular matrix is the dominant contributor to whole muscle and fascicle passive tension. They also demonstrate that caution should be used when inferring whole muscle properties from reduced muscle size preparations such as muscle biopsies.